A short review on mechanical and barrier properties of polylactic acid-based films. (2022) - Mohan, S.; Panneerselvam, Kavan
Abstract: Polylactic acid (PLA), is a biodegradable plastic derived from renewable resources, and therefore it is a substitute for many conventional petroleum-based polymers. PLA has very good properties like excellent mechanical strength, great modulus, biodegradability, biocompatibility, bio absorbability, energy savings, less harmfulness, and easily processable. Owing to these properties PLA based composite films have been huge attention in Food Packaging (FP) applications. This paper reviews the mechanical and Barrier Properties (BP) of PLA based composite films investigated by the different researchers, and some of them have been discussed here. The widespread adoption of PLA composite films is limited by high brittleness, BP, poor thermal stability and less elongation. To overcome this, an enormous amount of research has been done on PLA based composite films by adding various organic, inorganic, and essential oil fillers. According to this study, PLA has the potential to be used in the synthesis of composite films.